FRESH TO CUP COFFEE BUSINESS PLANNING AND DEVELOPMENT IN WEST JAVA USING THE TRIPLE LAYERED BUSINESS MODEL CANVAS - Rezky, Dikanio; Mulyadi, Hari; Utama, Dian; Furqon, Chairul (Jurnal Riset Bisnis dan Manajemen, 2025)
This study designs a fresh-to-cup coffee business development model in West Java using the Triple Layered Business Model Canvas (TLBMC) approach. The main problem is the lack of implementation among coffee MSMEs in integrating sustainability into their business models. The research, conducted through a case study on MSMEs in Cimahi City, combines SWOT analysis, IFAS and EFAS matrices, and Plus Minus Implication Analysis (PMIA). Findings show strengths in product quality, marketing, and social impact, but weaknesses in space, distribution, and waste management. The IE matrix positions the business in the "Grow & Build" quadrant, recommending product expansion. TLBMC successfully integrates economic, environmental, and social sustainability dimensions, though some areas require improvement. PMIA results show positive potential in each sustainability dimension, highlighting opportunities for long-term business success. Overall, TLBMC provides strategic guidance for MSMEs to create sustainable economic, environmental, and social value.